Modification of Coronary artery disease (Macroangiopathy) in Type II DM patient by intervening microalbuminuria - Ali, MZ; Ali, SMK; Khan, AKA (University Heart Journal, 2008)
Cardiovascular disease are major burden in patients with T2DM causing work unfitness, disability and premature death. In order to establish, microalbuminuria as a modifiable risk factor for these conditions. The present study was conducted by intervening with ACE inhibitor, antioxidant, antithrombotic as modifiable agents of microabluminuria in T2DM Patients. The study was randomized control trial. We selected 1605 T2DM Patients of 40-50 years by pre-determined criteria from OPD of BIRDEM. By estimating microalbuminuria we included 368 as study group (> 300mg/day) and 682 as control group (< 300mg/day). The following parameters were the key variables, duration of diabetes, FBG, Total cholesterol, HDL, blood pressure and ECG at entry and after 18 Months. The mean SD age duration of diabetes in microabuminuric and nonmicroalbuminuric subject were 45.67 3.98, 3.78 3.14 and 45.45 3.98, 72 3.04 respectively. The microalbuminuric group showed statistically significant difference (p< 0.005) in the following parameters FBG, HBA1C, SBP, DBP, T- cholesterol in comparison to nonmicroalbuminuric group. Nonmicroalbuminuric subjects showed the deterioration in HDLc, LDLc and a conversion rate of 21.7% from nonmicroalbuminuric to microalbuminuric. ACE inhibitor, Antioxidant and Antithrombotic are advantageous to conventional therapy for T2DM patients with in IHD as evident by this intervent ion. The achieving improvement were 68.50% for those conditions. University Heart Journal Vol.4(1) January 2008